hi all, given the implicit equation $\displaystyle x^2+x+1-y^2 = 0$, how can i find the parametric form of this equation, i.e.: x = f(t) y = f(t) thanks in advance for the help.
Follow Math Help Forum on Facebook and Google+
Originally Posted by tombrownington hi all, given the implicit equation $\displaystyle x^2+x+1-y^2 = 0$, how can i find the parametric form of this equation, i.e.: x = f(t) y = f(t) thanks in advance for the help. Note: 1. Your cartesian equation can be re-written as $\displaystyle \frac{4}{3} \left( x + \frac{1}{2} \right)^2 - \frac{4}{3} y^2 = -1$. 2. From the Pythagorean Identity: $\displaystyle \tan^2 t - \sec^2 t = -1$.
View Tag Cloud